Kierkegaard - Adorno, Theodor W. 1903-1969 (Darmstadt Wissenschaftliche Buchgesellschaft, 1998)
Philosopher, sociologist, and musicologist, Adorno (1903-1969) published this as his first major work in 1933. By then he had been studying Kierkegaard for nearly 20 years and would continue to refer to the life and work of the 19th-century Dane throughout his own intellectual career. For Kierkegaard, the aesthetic is the first of three stages in one's interior development, and Adorno concerns himself with revealing the not-always-conscious course by which Kierkegaard came to this formulation. While of importance to scholars of existentialism, intellectual history, and Adorno, this book is not for lay readers.- Francisca Goldsmith, Berkeley P.L., Cal.Copyright 1989 Reed Business Information, Inc. --This text refers to an out of print or unavailable edition of this title.
Keywords: Kierkegaard, Søren -- 1813-1855; 19th Century (1801-1900); Philosophy; Denmark